Detection of pathogenic Vibrio in the ballast water by polymerase chain reaction - Huo, Ying-Yi; Xu, Xue-Wei; Wang, Chun-Sheng; Huang, Lei; Wu, Gang; Wu, Min (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2010)
The potential of ballast water to act as a major vector for invasive alien species has long been recognised. Invasive alien species caused by ballast water frequently outcompete or prey on native species and spread diseases to plants, animals, and human. They often encroach on, damage, or degrade assets and result in significant economic impacts. Vibrios are highly abundant in marine environments. Some of them such asVibrio cholerae, V. vulnificus and V. parahaemolyticusare pathogenic for human being. An international ballast water performance standard, which prescribedVibrio cholerae(O1 and O139) with less than 1cfu per 100 mL, was adopted by the International Maritime Organization (IMO) in 2004. Multiple pathogens in ballast water samples from Zhoushan archipelago located in the eastern of China were detected. Two virulence-associated genes (hly Aandvvh) usually fromV. cholerae and V. vulnificuswere detected by polymerase chain reaction. The molecular library containing 16S rRNA gene ofVibriowas constructed